Sex As A Form of Gender and Expression After Lawrence v. Texas - Garland, James Allon (Columbia Journal of Gender and Law, 2006)
The Supreme Court’s decision in Lawrence v. Texas has been touted in many circles as a significant gay rights opinion, but it is much more than that. While it is certainly the first decision of the Court to recognize a constitutionally protected interest in same-sex intimacy, it is even more significant as the first opinion from the Court to speak positively about sex without reference to procreation, recognizing that sex can be a valuable form of “expression” that “can be but one element in a personal bond that is more enduring.”‘ The reference is brief and unexplained, but has greater constitutional resonance when compared to the Court’s prior relegation of sex to “myster[y]” and a “sensitive, key relation to human existence.” The Court’s willingness to characterize sex as a possible form of expression is particularly remarkable, considering how little judicial and scholarly support the argument has found. For some, it may be difficult to accept that sex could be communicative without a public audience, even though the Court has held that private communication, such as a conversation, is protected by the First Amendment. For others, only traditional coital sex expresses appropriate values, even though it is precisely this attempt to monopolize conduct for a particular point of view that triggers strict scrutiny of conduct alleged to express ideas.” Or perhaps it is all that sex entails-the physical exertion, the concentration on technique, the sweat, the noises and curious silences, the pursuit of orgasm, the hope or fear of procreation, and frankly sometimes simply too much or too little going on wherever it all takes place-that just seems so unusual for “speech,” making a mess of the idea of expression in the midst of sex, or at least sex as some know it.